PKM Kewirausahaan Pengolahan Ubi Kayu Menjadi Keripik Singkong - Ika Wisudawaty; Hasbi Hasbi; Mahmuddin Mahmuddin; Muh. Rizah Putrawan; Fitrah Widya Wati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Cassava is a food crop that has many advantages and can be an added value to increase the durability of cassava so that it is suitable for consumption and by utilizing cassava it obtains a high selling value on the market. Added value is the addition of value to a product before the production process is carried out and after the production process is carried out. Processing cassava into cassava chips is to increase the durability of the cassava so that it is suitable for consumption and to utilize the cassava to obtain a high selling value for marketing. Cassava chips are a snack product that many consumers like. The crunchy taste and cheap price offered make this product a suitable alternative to accompany relaxing time with family, co-workers, friends, and so on. Even though cassava has many advantages, including its ability to grow in difficult conditions, the price of cassava in Indonesia is still low compared to other staple crops. Therefore, innovation is needed to increase the selling value of cassava. One way to add value is to process cassava into cassava chips, which is a popular snack among people, especially teenagers. Cassava chips have a distinctive and crunchy taste, and the processing process provides added value to cassava